The Effectiveness Of On-Site Detention For Water Quantity Control In Taman Ilmu Using Stormwater Management Model (SWMM) - Tan, Zi Guan (Universiti Sains Malaysia, 2018)
Rapid urbanisation causes the risk of flood to increase due to large impervious surface area. On-site detention is introduced as a flood mitigation in this study. The objectives of the study are to model Taman Ilmu drainage system using Stormwater Management Model and to evaluate the effectiveness of on-site detention. On-site detention is one of stormwater management device which detained the runoff to reduce the peak discharges and delay the flood. Stormwater Management Model is a widely used program for planning, analysis and design related to drainage systems of runoff quantity and quality in urban areas. Taman Ilmu is chosen as a study area because it is located beside the Kerian River which has the risk of flood occurring due to monsoon rain incorporate with rising tide. Over this study, 1 hour storm duration is used for design rainfall intensity and 79.03 mm/hr for 10 year ARI is calculated. After installation of OSD in each sub-catchment, the range of flow attenuation is from 22.5% to 89.2% due to different impervious area and volume of OSD. The results show that 48% attenuation of peak discharge from 2.189 m3/s to 1.137 m3/s at outlet of Taman Ilmu. The location and number are factors that can affect the effectiveness of OSD. Location of OSD at upstream area more effective than downstream. The number of OSD increase, the flow attenuation increase but the cost of installation and maintenance increase as well.